2021
DOI: 10.3390/machines9030051
|View full text |Cite
|
Sign up to set email alerts
|

Developing New Thermal Protection Method for AC Electric Motors

Abstract: Monitoring the thermal state of windings of electrical machines is a backbone for protection from unacceptable overheating. A large number of different methods and systems aim to solve this problem. This article discusses the main known methods of thermal protection of electric motors and provides their comparative analysis. This paper shows that the most promising methods are those based on control of the current active resistance of the stator winding, as its value uniquely depends on temperature. It is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The practical significance consists of the research of the automation system having been carried out and the structure of the electric drive having been studied on an industrial robot, which affects the quality of obtaining a welding seam. A six-axis robot manipulator MH50-35 [6], [7] model of the company Yaskawa was chosen as a basic industrial robot, the parameters of which are shown in Table 1. This robot is universal and was designed to execute a wide range of tasks, such as transferring objects and welding operations.…”
Section: Methodsmentioning
confidence: 99%
“…The practical significance consists of the research of the automation system having been carried out and the structure of the electric drive having been studied on an industrial robot, which affects the quality of obtaining a welding seam. A six-axis robot manipulator MH50-35 [6], [7] model of the company Yaskawa was chosen as a basic industrial robot, the parameters of which are shown in Table 1. This robot is universal and was designed to execute a wide range of tasks, such as transferring objects and welding operations.…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to calculate and estimate the typical fluid velocity U 0 when comparing the buoyancy effect and the thermal diffusion coefficient. When the fluid is guided only by buoyancy, according to the Grashof number, its typical velocity U 0 can be estimated, as given in (4).…”
Section: Theory Of Multi-physical Field Analysismentioning
confidence: 99%
“…Relying on online monitoring, it is found that the temperature distribution of various parts of the transformer is not uniform during operation [4]. The durability and service life of transformers would be reduced once it is overheated locally [5].…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent thermal parameters (thermal conductivity [14,15] heat transfer coefficients [16,17]) are often historically defined as empirical values based on the comparison of the calculation and measurement. The same methodology is also used in [18,19].…”
Section: Introductionmentioning
confidence: 99%